Snow contribution to first‐year and second‐year Arctic sea ice mass balance north of Svalbard. Issue 3 (29th March 2017) - Granskog, Mats A.; Rösel, Anja; Dodd, Paul A.; Divine, Dmitry; Gerland, Sebastian; Martma, Tõnu; Leng, Melanie J.
Abstract: The salinity and water oxygen isotope composition (δ 18 O) of 29 first‐year (FYI) and second‐year (SYI) Arctic sea ice cores (total length 32.0 m) from the drifting ice pack north of Svalbard were examined to quantify the contribution of snow to sea ice mass. Five cores (total length 6.4 m) were analyzed for their structural composition, showing variable contribution of 10–30% by granular ice. In these cores, snow had been entrained in 6–28% of the total ice thickness. We found evidence of snow contribution in about three quarters of the sea ice cores, when surface granular layers had very low δ 18 O values. Snow contributed 7.5–9.7% to sea ice mass balance on average (including also cores with no snow) based on δ 18 O mass balance calculations. In SYI cores, snow fraction by mass (12.7–16.3%) was much higher than in FYI cores (3.3–4.4%), while the bulk salinity of FYI (4.9) was distinctively higher than for SYI (2.7). We conclude that oxygen isotopes and salinity profiles can give information on the age of the ice and enables distinction between FYI and SYI (or older) ice in the area north of Svalbard. Plain Language Summary: The role of snow in sea ice mass balance is largely two fold. Firstly, it can slow down growth and melt due to its high insulation and high reflectance, but secondly it can actually contribute to sea ice growth if the snow cover is turned into ice. The latter is largely a consequence of high mass of snow on top of sea ice that can push the surface of the sea ice below sea level and seawater can flood the ice. This mixture of seawater and snow can then freeze and add to the growth of sea ice. This is very typical in the Antarctic but not believed to be so important in the Arctic. In this work we show, for the first time, that snow actually contributes significantly to the growth of Arctic sea ice. This is likely a consequence of the thinning of the Arctic sea ice. The conditions in the Arctic, with thinner and more seasonal ice thus resemble the ice pack in the Antarctic. Studies on the role of snow in the Arctic are critical to be able to understand the ongoing changes of the Arctic sea ice pack. Key Points: Snow contributed 7.5–9.7% (by mass) in a thinner Arctic sea ice pack north of Svalbard in winter and spring Second‐year ice contained significantly more snow than first‐year ice (12.7–16.3% versus 3.3–4.4%) With thinner Arctic sea ice, the snow:ice thickness ratio is similar than in the Antarctic, increasing the potential for snow‐ice formation